Dual-Echo Arterial Spin Labeling for Brain Perfusion Quantification and Functional Analysis - Paschoal, André Monteiro; Leoni, Renata Ferranti; Paiva, Fernando Fernandes (Concepts in magnetic resonance. Part A, Bridging education and research, 2019)
Arterial Spin Labeling (ASL) is a noninvasive MRI-based method to measure cerebral blood flow (CBF). Recently, the study of ASL as a functional tool has emerged once CBF fluctuation comes from capillaries in brain tissue, giving a more spatially specific response when compared to the standard functional MRI method, based on the blood oxygenation level-dependent (BOLD) contrast. Although the BOLD effect could be desirable to study brain function, if one aims to quantify CBF, such effect is considered contamination that can be more attenuated if short TE value is used in the image acquisition. An approach that provides both CBF and function information in a simultaneous acquisition is the use of a dual-echo ASL (DE-ASL) readout. Our purpose was to evaluate the information provided by DE-ASL regarding CBF quantification and functional connectivity with a motor task. Pseudocontinuous ASL of twenty healthy subjects (age: 32.4 ± 10.2 years, 13 male) was acquired at a 3T scanner. We analyzed the influence of TE on CBF values and brain connectivity provided by CBF and concurrent BOLD (cc-BOLD) time series. Brain networks were obtained by the general linear model and independent component analysis. Connectivity matrices were generated using a bivariate correlation (Fisher Z values). No effect of the sequence readout, but significant effect of the TE value, was observed on gray matter CBF values. Motor networks with reduced extension and more connections with important regions for brain integration were observed for CBF data acquired with short TE, proving its higher spatial specificity. Therefore, it was possible to use a dual-echo readout provided by a standard commercial ASL pulse sequence to obtain reliable quantitative CBF values and functional information simultaneously.